PENGGUNA PERPUSTAKAAN DI ERA DIGITAL DALAM PERSPEKTIF FENOMENOLOGI - Soetjiatie, Liliek (Metafora: Education, Social Sciences and Humanities Journal, 2015)
This   study would like to get an idea of the meaning of informants for library users ( user ) library ,  virtual  library user behavior change and the  ideal  library  is  analyzed  in   depth interview  with  the  student  Elektromedical  Engineering Program , Dental Nursing , Nursing and Midwifery Health Polteknik Kemenkes Surabaya on campus Surabaya. Informants  were  taken by  purposive  sampling  technique  based  on  the  research objectives . Analysis  of  the  data  using  a  phenomenological   perspective ,  where   the  subjective  meaning  of  each  behavior  produces   intersubjective     interpretation  of  an  event  given  each  subject  in this  case  is  the user  library as a free persona  choice in determining the appropriate necessities of life . This   study   suggests  that  there  has  been a  process  of  formation  of  system  relevance  in  the process of social interaction . That individuals   in  this  study were  students  in  determining   the  behavior  of  his  actions   as  humans   living  in  the  modern era  have  freedom  including  the  use of  the library , not lost in   cyberspace   huforia   promising    a  wealth  of  information   with   electronic   capabilities  possessed , but still need a conventional library which has advantages in different angle.